Peningkatan Kualitas Hasil Belajar Ekonomi Melalui Metode Student Team Achievement Divisions (Stad) Pada Siswa Kelas X S2 Ma Al-Islam Jamsaren Surakarta Tahun Ajaran 2016/2017 - Pramana, Thoha, Prof. Dr. Harsono, SU (2017)
This study aims to improve the results of economic learning through the Student Team Achievement Divisions (STAD) method on the students of class X S2 MA Al-Islam Jamsaren Surakarta academic year 2016/2017. This type of research is aclassroom action research conducted in two cycles. The subjects of the study were the teachers who gave the action and herecipients of the action. The students were the students of Grade X S2 MA Al-Islam Jamsaren Surakarta, amounting to 26 students. Data collection methods used were interviews, observation, tests, documentation and field notes. Data analysis echnique is used descriptive technique of comparative and critical analysis technique. The result of the research showed that the improvement of students' economic learning outcomes in the first cycle was 46% and in the second cycle was 84.62%. So it can be concluded that the implementation of Student Team Achievement Divisions method can improve the economic learning outcomes in the students of class X S2 MA Al-Islam Jamsaren Surakarta academic year 2016/2017.